Antioxidants in radioprotection – methods of free radicals detection and identification - Rożej, Adam; Małkowski, Bogdan; Andryskowski, Grzegorz; Tryniszewski, Wiesław; Maziarz, Zbigniew (Contemporary Oncology/Współczesna Onkologia, 2000)
Discovery of X radiation in 1895 as well as isolation of pure radium in 1902 by Marie and Pierre Curie resulted in the development of new diagnostic and therapeutic methods. The phenomenon of ionization accompanying radiation may be harmful and dangerous however, its proper use in a planned and controlled way serves for saving human life. Technical parameters of the apparatus, exposure time, distance from the source or application of protective shield are of unquestionable importance in radiological protection. Application of radioprotective substances in irradiated persons is one of the elements of radioprotection having so far little practical importance. The aim of the study was survey assessment of available scientific research on the effect of antioxidative substances on morphological and biochemical parameters of living organisms subjected to ionizing radiation. Having analysed the presented studies, there arises a question whether active substances demonstrating positive effect on irradiated organisms will find practical application in complementary therapy of irradiated patients and whether they will be of significance in medical staff and their patients radioprotection.